2017
DOI: 10.1007/s12015-017-9747-z
|View full text |Cite
|
Sign up to set email alerts
|

Lung as a Niche for Hematopoietic Progenitors

Abstract: Platelets are released from megakaryocytes. The bone marrow has been proposed to be the major site where this process occurs. Lefrançais et al. (2017) using state-of-the-art techniques including two-photon microscopy, in vivo lineage-tracing technologies, and sophisticated lung transplants reveal that the lung is also a primary site for platelet biogenesis. Strikingly, lung megakaryocytes can completely reconstitute platelet counts in the blood in mice with thrombocytopenia. This study also shows that hematopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 112 publications
1
39
0
1
Order By: Relevance
“…However, it remains unclear whether this priming needs direct contact between osteoblasts and neutrophils, or whether it depends on molecules secreted by osteoblasts to the bone marrow milieu or even to the circulation that will induce the formation of SiglecF high –expressing neutrophils. Interestingly, a recent study showed that the lung microenvironment serves as a niche to a subtype of hematopoietic stem cells that produce all hematopoietic lineages, including neutrophils [83,84]. It remains unknown whether the neutrophils produced in the lung are also primed by the bones through osteoblasts-derived molecules present in the circulation, and what percentage of tumor promoting SiglecF high – expressing neutrophils originate from the lung.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…However, it remains unclear whether this priming needs direct contact between osteoblasts and neutrophils, or whether it depends on molecules secreted by osteoblasts to the bone marrow milieu or even to the circulation that will induce the formation of SiglecF high –expressing neutrophils. Interestingly, a recent study showed that the lung microenvironment serves as a niche to a subtype of hematopoietic stem cells that produce all hematopoietic lineages, including neutrophils [83,84]. It remains unknown whether the neutrophils produced in the lung are also primed by the bones through osteoblasts-derived molecules present in the circulation, and what percentage of tumor promoting SiglecF high – expressing neutrophils originate from the lung.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…The decisions of stem cells to continue quiescent, self‐renew, or differentiate are dependent on the interaction of these cells with other cells in their surrounding niches . Recently, multiple cell types have been identified as potential niche‐supporting cells for stem cells in the skin .…”
Section: Schwann Cells Plasticity In the Skinmentioning
confidence: 99%
“…Genetically modified mice have been widely applied to study cell types within diverse tissues microenvironments (Borges and others 2017; Lousado and others in press). The ability to delete single genes in specific cell types in adult mice has allowed us to answer specific questions regarding the roles of different cell populations in the regulation of several physiologic and pathologic processes (Andreotti and others 2017).…”
Section: Targeting Pericytesmentioning
confidence: 99%